Students’ Preference between Off-Campus Cafes vs Campus Space for Group Studies - Dahal, Aashish; Bharati, Diya; Subedi, Kopila; Roka, Rajika; Lamichhane, Sanju; Bhandari, Utsav; Parajuli, Suman kamal (International Journal of Education, Management, and Technology, 2025)
This study investigates student preferences for off-campus cafes versus on-campus spaces as venues for group study, focusing on factors such as noise and distraction, social interaction, facilities, and overall productivity. Guided by a positivist philosophy and a deductive approach, the research adopts a descriptive and comparative design to analyze quantitative data from 141 college students collected through a structured self-administered questionnaire. Results indicate a general preference for off-campus cafes due to their comfortable atmosphere, robust digital facilities such as Wi-Fi and charging ports, and a social ambiance that fosters group interaction. However, cafes are also perceived as more distracting because of higher noise levels. In contrast, on-campus spaces are valued for access to academic resources, a motivating academic environment, and suitability for quiet, focused group work. Paired sample t-test results confirm significant differences in preferences between the two settings. The findings suggest that students choose study environments according to their specific needs seeking social engagement and comfort in cafes, and academic support and concentration on campus. The study recommends that educational institutions integrate both social and academic features in study space design to accommodate diverse learning styles and collaborative needs.